Lupus-related protein-losing enteropathy associated with pseudo-pseudo Meigs' syndrome and successfully treated with hydroxychloroquine - Horino Taro; Ogasawara Masami; Kashio Takeshi; Inotani Satoshi; Ishihara Masayuki; Ohnishi Hiroshi; Komori Masahiro; Ichii Osamu; Terada Yoshio (Sciendo, 2022)
We herein report the first case of lupus-related protein-losing enteropathy associated with pseudo-pseudo Meigs' syndrome. Lupus-related protein-losing enteropathy and pseudo-pseudo Meigs' syndrome are extremely rare complications in patients with systemic lupus erythematosus, Both have a similar clinical course characterized by producing marked ascites, and respond to steroids in typical cases. However, in our case, steroid monotherapy was inadequate and the addition of hydroxychloroquine was effective for their treatment. Furthermore, no reports have previously confirmed elevated CA 125 levels with lupus-related protein-losing enteropathy or increased 99mTc-HSA activity with pseudo-pseudo Meigs' syndrome. In addition, we are the first to report an evaluation of the histopathology of lupus-related protein-losing enteropathy. Previously reported cases have been described as being caused by either pseudo-Meigs's syndrome or lupus-related protein-losing enteropathy as the cause of the rare pathology that causes marked pleural effusion and ascites in patients with systemic lupus erythematosus, but it has not been evaluated whether the other is co-occurring. Our case highlights that there is a potential case of overlapping lupus-related protein-losing enteropathy and pseudo-Pseudo-Meigs's syndrome. Furthermore, it is possible that patients with marked ascites with elevated CA 125 levels were mistakenly diagnosed with Meigs's syndrome or pseudo-Meigs's syndrome associated with malignant or benign ovarian tumors and underwent surgery. Clinicians should not forget SLE with pseudo-Pseudo-Meigs's syndrome as one of the differential diagnoses for marked ascites with elevated CA 125 levels.